Use of Flashcard Media to Improve English Vocabulary of Fourth Grade Students of Muhammadiyah Gunung Lagan Elementary School - Hati, Puspita; Mardiana (MANDAILING GLOBAL EDUKASIA, 2025)
This study aims to analyze and measure the effectiveness of using flashcards to improve English vocabulary mastery among fourth-grade students at Muhammadiyah Gunung Lagan Elementary School. The background of the problem indicates that fourth-grade students often encounter difficulties and lack motivation in memorizing English vocabulary, which impacts suboptimal learning outcomes. This weakness is strongly suspected to stem from monotonous conventional learning methods, a lack of media variety, and minimal visualization. To address these issues, this study adopted a Classroom Action Research (CAR) approach, implemented through two cycles. Each cycle consisted of four stages: planning, implementation, observation, and reflection. The subjects were 25 fourth-grade students at Muhammadiyah Gunung Lagan Elementary School. Data were collected through observations of student activity during the learning process and learning outcome tests (pre-test and post-test) in each cycle. The results showed significant improvement. In Cycle I, the percentage of classical completion reached 68%, with room for improvement. After corrective actions in Cycle II, the percentage of classical completion increased sharply to 88%, exceeding the established success indicator (the school's Minimum Completion Minimum). Furthermore, observations showed a positive increase in student activity and enthusiasm. Therefore, it can be concluded that the use of flashcards has proven effective and is suitable as an innovative solution to improve the English vocabulary mastery of fourth-grade students at Muhammadiyah Gunung Lagan Elementary School.